Prognosis for babies born with fused eyelids. Issue 5 (May 1985) - Cross, G; Becker, M; Congdon, P
Abstract : The overall mortality for babies referred to our unit with fused eyelids was 68.7%; but when severe skin bruising was present only one of 18 babies survived (5.6%). This compares with a survival rate of 75% for those not bruised at or soon after birth. Skin bruising invariably indicates a very poor prognosis in babies born with fused eyelids.